Median preoptic nucleus mediates the cardiovascular recovery induced by hypertonic saline in hemorrhagic shock - Amaral, Nathalia Oda; Naves, Lara Marques; Ferreira-Neto, Marcos Luiz; Freiria-Oliveira, André Henrique; Colombari, Eduardo [UNESP]; Rosa, Daniel Alves; Reis, Angela Adamski da Silva; Ianzer, Danielli; Xavier, Carlos Henrique; Pedrino, Gustavo Rodrigues (Hindawi, 2014)
Changes in plasma osmolarity, through central and peripheral osmoreceptors, activate the median preoptic nucleus (MnPO) that modulates autonomic and neuroendocrine adjustments. The present study sought to determine the participation of MnPO in the cardiovascular recovery induced by hypertonic saline infusion (HSI) in rats submitted to hemorrhagic shock. The recordings of mean arterial pressure (MAP) and renal vascular conductance (RVC) were carried out on male Wistar rats (250–300 g). Hemorrhagic shock was induced by blood withdrawal over 20 min until the MAP values of approximately 60 mmHg were attained. The nanoinjection (100 nL) of GABAA agonist (Muscimol 4 mM; experimental group (EXP)) or isotonic saline (NaCl 150 mM; control (CONT)) into MnPO was performed 2 min prior to intravenous overload of sodium through HSI (3 M NaCl, 1.8 mL/kg, b.wt.). Hemorrhagic shock reduced the MAP in control (62 ± 1.1 mmHg) and EXP (61 ± 0.4 mmHg) equipotently. The inhibition of MnPO impaired MAP (CONT: 104 ± 4.2 versus EXP: 60 ± 6.2 mmHg) and RVC (CONT: 6.4 ± 11.4 versus EXP: −53.5 ± 10.0) recovery 10 min after HSI. The overall results in this study demonstrated, for the first time, that the MnPO plays an essential role in the HSI induced resuscitation during hypovolemic hemorrhagic shock.